The moderating effect of audit quality on the relationship between environmental, social, and governance scores and corporate financial performance of listed companies in the ASEAN-5 - Cheng, Michaela Nicole U. (Animo Repository, 2023)
A number of corporate accounting scandals have had effects that trickled down to the daily lives of ordinary people. These occurrences emphasize the need for high-quality audits to assure the reliability of an entity’s financial statements. There are other means of building trust and commitment between a company and its stakeholders. One of these is through environmental, social, and governance (ESG) activities, which open opportunities for stakeholder engagement. Consequently, they have been presumed to impact a company’s financial performance. Research on corporate social responsibility (CSR), an enrichment of ESG, shows related studies in developing countries are undertheorized. The lack of research, combined with relatively weak legislation and motivations, presents the need for more studies in developing areas such as the ASEAN-5. The study aims to investigate the effect of ESG scores on corporate financial performance (CFP) of listed companies in the ASEAN-5 and the moderating effect of audit quality on the relationship between ESG scores and the corporate financial performance of listed companies in the ASEAN-5. In the past, related studies have shown conflicting results. Audit quality is proxied by the auditor’s identity (Big-4/non-Big-4). CFP is gauged by the return on assets, return on equity, and Tobin’s Q. Secondary data were acquired from the listed companies’ official annual reports and Refinitiv Eikon. The study has a causal design, and multivariate regression analyses were used to analyze the gathered data. The results showed that ESG scores have a significant effect on the CFP measures. Big-4 auditor, as a moderating variable, has a significant effect on the relationship between ESG scores and CFP measures. On the other hand, non-Big-4 auditor has an insignificant effect on the aforementioned relationship.